A lithium metal negative electrode material and preparation method thereof
By constructing the interface layer between fluorinated carbon and organic components on the surface of lithium metal, the problems of uneven deposition and volume expansion of lithium metal negative electrode materials in traditional technology are solved, and the high energy density and safety performance of lithium metal batteries are achieved.
Patent Information
- Application Number
- CN202210919445.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-02
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-08-02
AI Technical Summary
The energy density of graphite negative electrodes in traditional lithium-ion batteries is limited, and the lithium metal negative electrode materials have problems such as uneven deposition, volume expansion and high reactivity during use, which limits its further development.
Spraying and in-situ lithiation reaction methods are used to construct an interface layer composed of fluorinated carbon and organic components on the surface of lithium metal. By adjusting the thickness and composition of the interface layer, uniform deposition of lithium metal and improvement of electrochemical properties are promoted.
The uniform deposition of lithium metal negative electrode material is achieved, the generation of lithium dendrites is reduced, the circulation and safety performance of the battery is improved, and it is suitable for lithium metal batteries under different working conditions.
Smart Images

Figure CN115249801B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium metal negative electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in electric vehicles, smart grids, portable electronic devices and other fields due to their advantages such as high specific energy, low self-discharge and no memory effect. However, with the rapid development of energy technology today, higher requirements are placed on the energy density and power density of lithium-ion batteries. Traditional lithium-ion batteries use graphite as the negative electrode material, but the theoretical specific capacity of graphite negative electrode is low (372mAh / g), and its energy density is difficult to exceed 300Wh·kg -1 This limit severely restricts its further development. Therefore, it is particularly important to develop negative electrode materials with higher specific capacity, such as silicon-based negative electrode materials and lithium metal negative electrode materials, to improve the energy density of batteries.
[0003] Lithium metal is known as the "holy grail" of negative electrode materials because of its extremely high theoretical specific capacity (3860 mAh / g), the lowest redox potential (-3.04 V relative to standard hydrogen electrode) and low density (0.534 g / cm 3 ) and other advantages. Therefore, the use of lithium metal as the negative electrode material can significantly improve the energy density of lithium-ion batteries. In addition, compared with lithium-ion batteries, lithium metal batteries can use positive electrode materials with higher energy density (such as sulfur, oxygen, etc.), so they can form a high specific energy battery system. However, there are some problems with lithium metal negative electrode materials during use, which seriously restricts its further development. These include the following points: First, the solid electrolyte interface film (SEI) generated on the surface of lithium metal is uneven, causing uneven deposition and stripping of lithium metal; second, there is a large amount of volume expansion of lithium metal during the deposition and stripping process, which further leads to the instability of SEI; third, the high reactivity of lithium metal and electrolyte leads to the continuous consumption of lithium metal and electrolyte.
[0004] In response to the above problems, researchers have studied them from different angles, such as electrolyte modification, current collector surface modification and lithium metal surface modification. But in essence, the biggest difference between electrochemical reactions and conventional chemical reactions is that electrochemical reactions all occur at the interface, and the regulation of the interface can have a decisive influence on the electrochemical reaction. In the interface modification of lithium metal, fluorinated SEI is recognized as an effective modification method for lithium metal anodes. For example, Tao Xinyong's research group [Advanced Material 2021, 33 (42), e2102134.] proposed to directly add porous LiF to the electrolyte to achieve stable and safe lithium metal batteries. Unlike traditionally designed electrolytes, the electrolyte prepared in porous LiF exhibits non-flammability and high electrochemical performance due to the strong interaction between the electrolyte solvent molecules and the large number of exposed active LiF (111) crystal faces. Zhang Qiang's research group [Angewandte Chemie International Edition 2021, 60(42), 22683-22687.] proposed to construct a stable anion-derived SEI by regulating the electrolyte structure of anions through anion receptors. The tri(pentafluorophenyl)borane anion receptor with electron-deficient boron atoms interacted with the bis(fluorosulfonyl)imide anion, thereby increasing the LiF content in the SEI and improving the stability of the SEI.
[0005] Existing research results show that constructing a fluorinated SEI can indeed effectively promote the uniform deposition of lithium metal and ultimately improve the cycle performance of lithium metal batteries. However, the traditional fluorinated SEI used in the prior art only increases the content of inorganic components in the SEI, and inorganic components have many disadvantages in terms of flexibility. In a complete lithium deposition process, the desolvation of lithium ions at the interface, the transport of lithium ions within the SEI, and the nucleation of lithium ions are all very important processes for lithium metal deposition, and simply increasing the content of LiF cannot coordinate and regulate these processes. Moreover, the existing technology for constructing a fluorinated SEI is too complicated. Although the sophistication of the experimental operation can increase the regulation of the interface components, it also increases the complexity of the overall preparation process, which is not conducive to large-scale production applications.
[0006] It can be seen from the above research results that further modification of the SEI interface of lithium metal negative electrode materials and improving the scalability of experimental methods are the key to solving the problems of traditional fluorinated SEI. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a lithium metal negative electrode material and a preparation method thereof.
[0008] The present invention provides a lithium metal negative electrode material, wherein the lithium metal negative electrode material has an interface layer on the surface of one side of the lithium metal, and the thickness of the interface layer is 100nm-100μm; the interface layer is obtained by dissolving carbon fluoride and an organic component in a volatile solvent, spraying them on the surface of the lithium metal, and then undergoing an in-situ lithiation reaction, and the organic component is obtained by adding a binder to a single ion conductor and mixing them evenly.
[0009] The present invention also provides a method for preparing a lithium metal negative electrode material. The preparation method is as follows: a binder and a single ion conductor are uniformly mixed as an organic component, and then carbon fluoride and the organic component are dissolved in a volatile solvent, and the solvent is sprayed onto one side of the lithium metal in a heated state of 120-170° C. using a spray gun, and the solvent on the surface of the lithium metal is completely evaporated, and the lithium metal negative electrode material is obtained by circulating for 3-5 times under low current conditions.
[0010] Furthermore, the binder is polyvinylidene fluoride, the single ion conductor is poly-2-acrylamide-2-methylpropane sulfonate lithium or lithiated polyborate; the polyvinylidene fluoride and poly-2-acrylamide-2-methylpropane sulfonate lithium or lithiated polyborate are uniformly mixed in a mass ratio of 1:9 as an organic component; the mass ratio of the carbon fluoride to the organic component is 1-4:1, and the volatile solvent is N-methylpyrrolidone or tetrahydrofuran.
[0011] Furthermore, the binder is polyvinylidene fluoride, the single ion conductor is poly-2-acrylamide-2-methylpropane sulfonate lithium; the polyvinylidene fluoride and poly-2-acrylamide-2-methylpropane sulfonate lithium are mixed evenly in a mass ratio of 1:9 as an organic component; the mass ratio of the carbon fluoride and the organic component is 2:1; and the volatile solvent is N-methylpyrrolidone.
[0012] Furthermore, the mass concentration of the carbon fluoride and the organic component dissolved in the volatile solvent is 1% to 20%.
[0013] Preferably, the mass concentration of the carbon fluoride and the organic component dissolved in the volatile solvent is 10%.
[0014] Furthermore, the spraying method of the spray gun is: use the spray gun to spray back and forth multiple times on the surface of one side of the lithium metal, and stop for half a minute after each spraying for half a minute to wait for the solvent to evaporate completely, and spray all the dispersion liquid back and forth in this way. The spraying time of the spray gun is 3min to 8min.
[0015] Preferably, the temperature at which the lithium metal is heated during spraying by the spray gun is 150°C.
[0016] Furthermore, the current density of the low current is 1 mA cm -2 .
[0017] Preferably, the low current condition is cycled for 5 times.
[0018] Beneficial effects of the present invention:
[0019] 1. The lithium metal battery negative electrode material provided by the present invention contains lithium fluoride and organic components in the interface layer on the surface of lithium metal, wherein lithium fluoride is obtained by in-situ lithiation of sprayed carbon fluoride, which can promote the uniform deposition of lithium metal, and the organic components can promote the desolvation of lithium ions and provide a stable lithium ion flow. The thickness of this interface layer is highly controllable, ranging from 100nm to 100μm, and can serve as a lithium metal protective layer. And the thickness of this interface layer can be controlled by adjusting the solvent concentration and the spraying time, and the different thicknesses of the interface layer can adapt to the different charging and discharging conditions of the lithium metal battery. When the existing lithium metal negative electrode material is used, the uncontrollable growth of lithium dendrites will not only generate dead lithium, causing the battery capacity to decline, but also may penetrate the diaphragm and cause safety accidents. The interface layer unique to the lithium metal negative electrode material of the present invention, lithium fluoride as the main inorganic component of the interface layer, has the largest interface energy with lithium, can promote the uniform deposition of lithium metal, thereby reducing the generation of lithium dendrites.
[0020] 2. The preparation method of the lithium metal negative electrode material provided by the present invention is to dissolve carbon fluoride and the selected organic component in a volatile solvent in a certain proportion, spray it on the surface of the heated lithium metal using a spray gun, and then complete the lithiation process after 3-5 cycles under low current conditions, preferably 5 cycles.
[0021] 3. The present invention determines that under the present preparation method, poly-2-acrylamide-2-methylpropane sulfonic acid is used as the main component of the organic component, and the effect is best when the ratio of carbon fluoride to organic component is 2:1. The present invention can greatly delay the migration of anions in the interface layer by using a single ion conductor, especially poly-2-acrylamide-2-methylpropane sulfonic acid as the organic component of the interface layer, thereby reducing the occurrence of side reactions. Due to the high reactivity of lithium metal, it is easy to parasitic reaction with various components in the electrolyte to generate a large number of by-products that are not conducive to lithium ion conduction, which gradually aggravates the failure of the battery. The organic component selected by the present invention has a certain flexibility, which helps to form a dense interface layer on the surface of lithium metal, avoid direct contact between lithium metal and electrolyte, and ensure the long-term stability of the lithium metal negative electrode.
[0022] 4. The present invention determines that under the present preparation method, the lithium metal is in a heated state of 150°C during spraying and the current density during the lithiation process is 1 mA cm -2 The effect is best when
[0023] 5. The lithium metal negative electrode material of the present invention has a wide range of applications. It can be used for all positive electrode materials currently used in commercial lithium-ion batteries. Commonly used positive electrode materials such as ion deintercalation materials, such as lithium iron phosphate, lithium cobalt oxide, and ternary positive electrodes can be used to pair with the lithium metal negative electrode material of the present invention to assemble batteries; some conversion materials, such as elemental sulfur, oxygen, air, etc., are also suitable for the lithium metal negative electrode material of the present invention.
[0024] 6. The present invention uses a combination of spraying and in-situ lithiation to construct an interface layer rich in lithium fluoride on the surface of lithium metal. Compared with the traditional method of constructing SEI by fluorination on the surface of lithium metal, on the one hand, the composition and thickness of the interface layer on the surface of lithium metal can be highly controllable. This controllable preparation method can meet the requirements of actual lithium metal batteries under different working conditions; on the other hand, the present invention does not require the purity of carbon fluoride, and can be carbonized from any fluorine-containing organic matter, and the raw material source is wide. The present invention achieves rapid lithium ion desolvation through the synergistic regulation of LiF and organic components, stabilizes the lithium ion flow and uniform lithium deposition in SEI, and thus greatly improves the electrochemical performance of lithium metal batteries. In addition, the spraying method required by the present invention is very easy to implement in industry, and can be directly coated on strip lithium metal, which can directly assemble laminated batteries or wound batteries, which is conducive to the large-scale production of lithium metal batteries and greatly promotes the research process of practical lithium metal. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a schematic diagram of the spraying method of the present invention;
[0026] Figure 2 1 is a scanning electron microscope photo of the lithium metal negative electrode material prepared in Example 1, the left side is a low-magnification scanning electron microscope photo, and the right side is a scanning electron microscope photo of the cross section of the prepared lithium metal negative electrode material;
[0027] Figure 3 The scanning electron microscope photographs of the common lithium foil of comparative example 1 are shown in FIG. 1 , with the left side showing a low-magnification scanning electron microscope photograph and the right side showing a high-magnification scanning electron microscope photograph;
[0028] Figure 4 The scanning electron microscope photographs of the lithium metal negative electrode material prepared in Comparative Example 2 are shown, with the left side showing a low-magnification scanning electron microscope photograph and the right side showing a high-magnification scanning electron microscope photograph;
[0029] Figure 5 The following are scanning electron microscope images of the lithium metal negative electrode material prepared in Comparative Example 3, with the left image being a low-magnification scanning electron microscope image and the right image being a high-magnification scanning electron microscope image;
[0030] Figure 6 The scanning electron microscope photographs of the lithium metal negative electrode material prepared in Comparative Example 4 are shown, with the left side showing a low-magnification scanning electron microscope photograph and the right side showing a high-magnification scanning electron microscope photograph;
[0031] Figure 7 The scanning electron microscope photographs of the lithium metal negative electrode material prepared in Comparative Example 5 are shown, with the left side showing a low-magnification scanning electron microscope photograph and the right side showing a high-magnification scanning electron microscope photograph;
[0032] Figure 8 The surface scanning electron microscope image of the lithium metal negative electrode material prepared in Example 1 after 100 cycles, the left side is a low-magnification scanning electron microscope image, and the right side is a high-magnification scanning electron microscope image;
[0033] Fig. 9 is a cross-sectional scanning electron microscope photograph of the lithium metal negative electrode material prepared in Example 1 after 100 cycles;
[0034] Fig.10 This is a scanning electron microscope photo of the common lithium foil of comparative example 1 after 100 cycles, the left side is a low-magnification scanning electron microscope photo, and the right side is a high-magnification scanning electron microscope photo;
[0035] Fig.11 This is a cross-sectional SEM photo of the common lithium foil of Comparative Example 1 after 100 cycles;
[0036] Fig.12 is a specific capacity-voltage curve diagram of the first five cycles of the lithiation process of the lithium metal negative electrode material prepared in Example 1;
[0037] Fig.13 It is a cycle performance curve diagram of a symmetrical battery assembled with lithium metal negative electrode materials prepared in Example 1 and Comparative Examples 1-5;
[0038] Fig.14 It is a cycle performance curve diagram of a full battery assembled with lithium metal negative electrode materials prepared in Example 1 and Comparative Examples 1-5;
[0039] Fig.15 This is a physical picture of a multilayer lithium metal soft-pack battery prepared by pairing the lithium metal negative electrode material prepared in Example 1 with lithium nickel cobalt manganese oxide;
[0040] Fig.16 This is a performance diagram of a multilayer lithium metal soft-pack battery prepared by pairing the lithium metal negative electrode material prepared in Example 1 with lithium nickel cobalt manganese oxide. DETAILED DESCRIPTION
[0041] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present application.
[0042] Example 1: Preparation of lithium battery negative electrode material using PAMPS-Li as the single ion conductor and a mass ratio of carbon fluoride to organic components of 2:1
[0043] Weigh a certain amount of PVDF (polyvinylidene fluoride) and PAMPS-Li (poly 2-acrylamide-2-methylpropane sulfonate lithium) in a mass ratio of 1:9, and mix them evenly as an organic component. Then weigh and mix the carbon fluoride powder and the above-mentioned organic component in a mass ratio of 2:1, and then disperse them in 10mL of NMP (N-methylpyrrolidone). Then place the lithium foil (area of 80 square centimeters) on the heating table in the glove box, heat the temperature to 150°C, take 2.5mL of dispersion into the spray gun, and spray it on the lithium foil in a back and forth path multiple times. After each half-minute spraying, it is necessary to stop for half a minute to wait for the solvent to evaporate completely. Repeat this process until all the dispersion is sprayed, and the solvent on the surface of the lithium foil is completely evaporated, and it can be made into a disc with a diameter of 12mm for standby use. The schematic diagram of the spraying is shown below. Figure 1 shown.
[0044] Subsequently, the lithium foil sprayed with lithium was heated to 1 mA / cm 2 The process was repeated for 5 cycles to prepare the lithium metal negative electrode material of the present invention. Figure 2 This is a scanning electron microscope photo of the lithium metal negative electrode material prepared in this embodiment. From the left figure, it can be seen that the carbon fluoride powder is completely embedded in the organic component mainly composed of PAMPS-Li and is evenly distributed. From the cross-sectional view on the right, it can be seen that the thickness of the interface layer is 800nm, which meets the requirements of artificial SEI. It shows that when the mass ratio of carbon fluoride powder to organic component is 2:1, the surface of the prepared lithium metal negative electrode material is relatively smooth, and carbon fluoride is embedded in the organic component with a thickness of about 800nm. Therefore, lithium fluoride can be constructed while establishing a conductive network, achieving uniform deposition of lithium metal.
[0045] Example 2 Single ion conductor, organic component mass ratio and reaction condition screening test
[0046] Using lithium poly-2-acrylamide-2-methylpropanesulfonate or lithiated polyborate as a single ion conductor, and N-methylpyrrolidone or tetrahydrofuran as a volatile organic solvent, a lithium metal negative electrode material was prepared according to the preparation method of Example 1, and these materials were scanned by an electron microscope. Unprocessed ordinary lithium foil was used as the lithium metal negative electrode material of the control group of Comparative Example 1 to verify the difference in the morphology of the lithium metal negative electrode materials prepared under different single ion conductors, different volatile organic solvents, different mass ratios of carbon fluoride and organic components, different heating temperatures, different lithiation current densities and different cycle numbers.
[0047] Table 1. Experimental design for screening reaction conditions of lithium metal negative electrode material preparation method
[0048]
[0049] Comparative Example 1
[0050] Ordinary lithium foil was used as lithium metal negative electrode material, and electron microscopy scanning was performed, such as Figure 3 As shown, it can be seen that the surface of ordinary lithium foil used as lithium metal negative electrode material is very smooth.
[0051] Comparative Example 2
[0052] Comparative Example 2: The lithium metal negative electrode material was prepared, and the electron microscope scanning was as follows: Figure 4 As shown, it can be seen that due to the small amount of carbon fluoride powder, the surface of the lithium metal negative electrode material is gel-like as a whole, and the reduction of inorganic components will reduce the ion conductivity of the entire interface layer.
[0053] Comparative Example 3
[0054] Comparative Example 3: The lithium metal negative electrode material was prepared, and the electron microscope scanning was as follows: Figure 5 As shown, it can be seen that when the addition ratio of carbon fluoride powder is increased, the gel-like surface of the lithium metal negative electrode material decreases, but exposed carbon fluoride powder also appears, which will detach from the interface layer, which is not conducive to the overall battery cycle performance.
[0055] Comparative Example 4
[0056] Comparative Example 4 prepared the lithium metal negative electrode material, and the electron microscope scanning was as follows Figure 6 As shown, it can be seen that when the proportion of carbon fluoride powder added is further increased, more and more carbon fluoride powder is exposed on the surface of the lithium metal negative electrode material, which will separate from the interface layer, which is extremely detrimental to the overall battery cycle performance.
[0057] Comparative Example 5
[0058] Comparative Example 5: The lithium metal negative electrode material was prepared, and the electron microscope scanning was as follows: Figure 7 As shown, it can be seen that when the single-ion conductor is replaced with lithiated polyborate, as long as the mass ratio of carbon fluoride powder to organic component is maintained at 2:1, spraying on the lithium metal surface can still present the morphology of carbon fluoride embedded in the organic component, which is beneficial to the later cycle.
[0059] from Figures 2 to 7 It can be seen that when preparing lithium metal negative electrode materials according to the method of the present invention, the ratio of carbon fluoride powder to organic components will affect the morphology of the interface layer generated on the surface of the prepared lithium metal negative electrode material. Too much carbon fluoride powder will lead to an uneven surface, and too much organic component will lead to a lack of certain mechanical strength. Only when the ratio is 2 to 1, as in Example 1, can the carbon fluoride powder be embedded between the organic components to achieve the best effect.
[0060] Example 3 Comparison of surface morphology changes of the lithium metal negative electrode material of Example 1 and the lithium foil of Comparative Example 1 after cycling
[0061] The lithium metal negative electrode material prepared in Example 1 and the lithium foil of Comparative Example 1 were cycled for 100 cycles and then scanned by electron microscope. Figure 8-11 shown.
[0062] Figure 8 This is a surface scanning electron microscope photo of the lithium metal negative electrode material prepared in Example 1 after 100 cycles. Compared with the original morphology ( Figure 8 Left), it can be seen that the surface morphology of the lithium metal negative electrode material prepared in Example 1 has not changed much after 100 cycles, maintaining the stability of the overall structure. And because the LiF generated in the interface layer can promote the uniform deposition of lithium metal, even after 100 cycles, there is still no lithium dendrite morphology on the surface. The colloid-like substance on the surface is the organic component sprayed on, and these colloid-like substances can alleviate the volume expansion of lithium metal during the cycle.
[0063] Fig. 9 This is a cross-sectional scanning electron microscope photograph of the lithium metal negative electrode prepared in Example 1 after 100 cycles. Due to the high reactivity and volume expansion effect of lithium metal, the uncontrollable growth of lithium dendrites will lead to the stacking of dead lithium, and then a layer of porous dead lithium and SEI mixed interface will be accumulated on the surface of the lithium metal active material. In Example 1, due to the effective suppression of lithium dendrites by LiF in the interface layer, the thickness of the surface dead lithium and SEI mixed interface is only 86μm after 100 cycles. It shows that the mass ratio of carbon fluoride powder to organic components selected in this embodiment is optimal. After 100 cycles, the surface of the lithium metal negative electrode has a smooth and dense morphology and no signs of lithium dendrites, and the thickness of the dead lithium and SEI mixed interface on the lithium metal surface is only 86μm.
[0064] Fig.10 This is a surface scanning electron microscope photograph of the lithium foil of Comparative Example 1 after 100 cycles as a lithium metal negative electrode material. It can be seen that the high reactivity and volume expansion of lithium metal lead to the porous structure of the lithium metal surface and the uncontrollable growth of lithium dendrites, which is not conducive to the cycle and safety performance of lithium metal batteries.
[0065] Fig.11This is a cross-sectional scanning electron microscope photo of the lithium foil of Comparative Example 1 after 100 cycles as a lithium metal negative electrode material. Due to the high reactivity and volume expansion effect of lithium metal, the uncontrollable growth of lithium dendrites will lead to the stacking of dead lithium, and then a layer of porous dead lithium and SEI mixed interface will be accumulated on the surface of the lithium metal active material. The untreated ordinary lithium foil of Comparative Example 1 cannot cope with the volume expansion of lithium metal, so the thickness of the surface dead lithium and SEI mixed interface is 280μm after 100 cycles.
[0066] Therefore, compared with ordinary lithium foil as a lithium metal negative electrode material, the lithium metal negative electrode material prepared by the method of the present invention can alleviate the volume expansion during the lithium metal cycle, reduce the uncontrollable growth of lithium dendrites, and reduce the thickness of the mixed interface between dead lithium and SEI on the lithium metal surface, thereby greatly improving the electrochemical performance and safety performance of lithium metal batteries.
[0067] Example 4 Determining the number of cycles during lithiation
[0068] The specific capacity-voltage curve of each cycle of the lithium metal negative electrode material prepared in Example 1 during the lithiation process at low current is shown in FIG. Fig.12 Since the sprayed carbon fluoride needs to undergo a certain lithiation process to generate lithium fluoride, a low current density lithiation process is introduced. This embodiment selects a current density of 1 mA / cm2. Too high a current density will result in incomplete lithiation, while too low a current density will have no practical significance. Fig.12 It can be seen from the first five cycles of the specific capacity-voltage curve that in the first cycle, carbon fluoride is converted into lithium fluoride, releasing a capacity of about 1050mAh, and the voltage platform of carbon fluoride at 2.3V and 1.5V is reflected, but it is not reflected in the subsequent cycles, indicating that the lithiation process of carbon fluoride is irreversible. It can be seen from the voltage curve of the third cycle that the entire lithiation process can no longer release too much capacity. In the fifth cycle, the lithiation process has stabilized, which means the success of the lithiation process. Therefore, it is preferred that five cycles be the number of cycles when the material is lithiation after spraying when preparing the lithium metal negative electrode material of the present invention.
[0069] Example 5 Comparison of the test results of lithium metal negative electrode materials of Example 1 and Comparative Examples 1-5 in symmetric batteries
[0070] Symmetrical cells were assembled with the lithium metal negative electrode materials of Example 1 and Comparative Examples 1-5, and the test conditions were a current density of 1 mA / cm 2 , deposition / dissolution capacity is 3mAh / cm 2 , the test results are as follows Fig.13 shown.
[0071] It can be seen that the symmetrical battery assembled with the lithium metal negative electrode material prepared in Example 1 has a high coulombic efficiency and stable cycle performance, and can maintain a stable cycle of 2000 hours under the condition of an overpotential of 10mV. However, the overpotential of the symmetrical battery assembled with lithium foil in Comparative Example 1 began to increase after 250 hours of cycling, and the inactive lithium on the surface gradually increased with the deepening of the cycle. The reaction byproducts of inactive lithium and lithium metal will increase the resistance to lithium ion transmission, and it will fail after 620 hours of cycling. The lithium metal negative electrode material prepared in Example 1 achieved the best cycle performance, which not only shows that the mass ratio of carbon fluoride powder to organic components is 2:1, but also shows that PAMPS-Li can show better electrochemical performance than lithiated polyborates.
[0072] Example 6 Comparison of the test of the lithium metal negative electrode materials of Example 1 and Comparative Examples 1-5 assembled into a full battery
[0073] The positive electrode material of lithium nickel cobalt manganese oxide is used as the positive electrode, the lithium metal negative electrode materials of Example 1 and Comparative Examples 1-5 are used as the negative electrode, 1 mol / L LiPF6 (EC:DMC, v / v=1:1) is used as the electrolyte, and Celgard2400 is used as the separator. The full battery is assembled for electrochemical performance testing. The performance is as follows Fig.14 As shown in the figure, it can be seen that the initial capacity of the full battery assembled with the lithium metal negative electrode material of Example 1 as the negative electrode is 187.8 mAh g -1 After 200 cycles, it can still maintain 151.8 mAh g -1 The discharge specific capacity has a very high capacity retention rate, which proves the cycle stability. However, the capacity of the full battery equipped with lithium foil in Comparative Example 1 decays rapidly with the deepening of the cycle, and the cycle stability is very poor. The lithium metal negative electrode materials prepared in Comparative Examples 2-5 have a better discharge specific capacity than Comparative Example 1, but are significantly lower than the lithium metal negative electrode materials prepared in Example 1. The lithium metal negative electrode material prepared in Example 1 not only has the best performance in symmetrical batteries, but also exhibits the most superior electrochemical performance in full batteries. It can still maintain 81.1% of the capacity after 200 cycles.
[0074] Example 7
[0075] A multilayer soft-pack battery was assembled using lithium nickel cobalt manganese oxide as the positive electrode material, the lithium metal negative electrode material prepared in step 1 as the negative electrode, 1 mol / L LiPF6 (EC:DMC, v / v=1:1) as the electrolyte, and Celgard 2400 as the separator. Fig.15 As shown, the electrochemical performance of the soft-pack battery in this layer is tested, and the performance is as follows Fig.16 As shown, the multi-layer soft pack battery can provide 330Wh kg -1The specific energy can be stably cycled for 100 times at a baseline capacity retention rate of 80%. Therefore, the lithium metal negative electrode material prepared in Example 1 has practical significance in production practice applications.
[0076] The above embodiments illustrate that even if the technical route of the present invention is adopted, the selection of single ion conductor, mass ratio of organic components and reaction conditions will have a substantial impact on the performance of lithium metal negative electrode materials. The technical solution of Example 1 can meet the needs of lithium metal negative electrode materials in production practice and is the best solution.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a lithium metal negative electrode material, characterized in that: The lithium metal negative electrode material has an interface layer on the surface of one side of the lithium metal, and the thickness of the interface layer is 100nm to 100μm; the interface layer is obtained by dissolving carbon fluoride and an organic component in a volatile solvent, spraying them on the surface of the lithium metal, and then undergoing an in-situ lithiation reaction, and the organic component is obtained by adding a binder to a single ion conductor and mixing them uniformly; the preparation method of the lithium metal negative electrode material is as follows: the binder and the single ion conductor are mixed uniformly as an organic component, and then the carbon fluoride and the organic component are dissolved in a volatile solvent, and a spray gun is used to spray them The lithium metal negative electrode material is sprayed onto the surface of one side of the lithium metal heated at 120-170°C, and the solvent on the surface of the lithium metal is completely evaporated. The material is circulated for 3-5 times under low current conditions to obtain the lithium metal negative electrode material. The binder is polyvinylidene fluoride, and the single ion conductor is poly-2-acrylamide-2-methylpropane sulfonate lithium. The polyvinylidene fluoride and poly-2-acrylamide-2-methylpropane sulfonate lithium are uniformly mixed in a mass ratio of 1:9 as an organic component. The mass ratio of the carbon fluoride to the organic component is 2:
1. The volatile solvent is N-methylpyrrolidone.
2. The method for preparing the lithium metal negative electrode material according to claim 1, characterized in that: The mass concentration of the carbon fluoride and the organic component dissolved in the volatile solvent is 1% to 20%.
3. The method for preparing the lithium metal negative electrode material according to claim 2, characterized in that: The mass concentration of the carbon fluoride and the organic component dissolved in the volatile solvent is 10%.
4. The method for preparing the lithium metal negative electrode material according to claim 1, characterized in that: The spraying method of the spray gun is: use the spray gun to spray back and forth multiple times on the surface of one side of the lithium metal, and stop for half a minute after each spraying for half a minute to wait for the solvent to evaporate completely, and spray all the dispersion liquid back and forth in this way. The spraying time of the spray gun is 3 minutes to 8 minutes.
5. The method for preparing the lithium metal negative electrode material according to claim 1, characterized in that: The temperature at which the lithium metal is heated during spraying by the spray gun is 150°C.
6. The method for preparing the lithium metal negative electrode material according to claim 1, characterized in that: The current density of the low current is 1 mA cm -2 .
7. The method for preparing the lithium metal negative electrode material according to claim 1, characterized in that: The low current condition was cycled for 5 cycles.
Citation Information
Patent Citations
Lithium metal negative pole preparation method, lithium metal negative pole and lithium battery
CN108039454A
Anode for lithium metal battery, method for manufacturing same, and lithium metal battery comprising same
WO2018124754A1